EFFECT OF STIRRING SPEED ON CADMIUM (Cd) METAL ADSORPTION FROM SASIRANGAN LIQUID WASTE BY RICE HUSK ACTIVATED CARBON - Isna Syauqiah; Desi Nurandini; Nopi Stiyati Prihatini; Rizki Azkia Simanjuntak (Universitas Lambung Mangkurat, 2021)
South Kalimantan is one of the textile industry producers, which is Sasirangan industry.The traditional fabric-making process involves chemicals as the production process. Sasirangan liquid waste contains pollutants that do not meet the requirements for disposal into the environment, including cadmium (Cd). Adsorption process is an effective method to reduce heavy metal concentrations in liquid waste. This study aims to determine the potential of rice husk activated carbon in adsorbing Cd metal from sasirangan liquid waste and to analyze the effect of stirring speed on the adsorption process. The rice husks that had been carbonized were then activated chemically and physically. Chemical activation process was carried out by adding chemical compound HCl which was immersed for 24 hours. Furthermore, it was physically activated in the furnace for 45 minutes at 4500C. In case to get optimum result, the effect of stirring speed on the adsorption process was studied. The stirring speed determines the rate of adsorbent and adsorbate contact time. The higher the stirring speed, the higher the decrease in Cd content because adsorbate absorption process by adsorbent is getting better. The greatest decrease in Cd concentration was by carbon that had been activated with a stirring speed of 90 rpm where the remaining Cd content in the sample was 0.018 mg / L.